Sosialisasi Kemasan Vakum untuk Penyimpanan Produk Ikan Asap dalam Upaya Pemberdayaan Masyarakat di Jatimurni, Bekasi - Daru Seto Bagus Anugrah; Rianita Pramitasari; Rakhdiny Sustaningrum; Ivana Mariska Sumitro; Stefano Capriati Winarno (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Residents of RT 003/RW 002 Jatimurni Village, Bekasi, have been running a tilapia fish-rearing business and attended training on processing tilapia into smoked fish. However, their understanding of using vacuum packaging to store and extend the shelf life of smoked fish products is still limited. This service aims to improve the community's understanding of the use of vacuum packaging and train the community's ability to use vacuum packaging equipment for smoked fish products. The method used was counselling and training. The results showed that after counselling, the community better understood the importance of vacuum packaging and could apply it to the smoked fish products produced.